ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUI AUDIT REPORT LAG PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - TEDJA, MARSELIA (Berkala Ilmiah Mahasiswa Akuntansi)
Investors and creditors need information for decision making, where information can be obtained from financial statements. Therefore, the financial statements should be presented on time so that they can immediately take a decision. In order to more reliable, after year end, the company will submit its financial statements to be audited by the independent auditors. Completion of the audit is time difference from the date of year end of the company until the date of signing the auditor's report referred to the audit report lag. This research aims to test the effect of firm size, auditor opinions, earnings or losses of the company, debt proportion, reporting extraordinary items and/or contingency to the audit report lag. The study design was quantitative with the hypothesis. Audit report lag measured by the number of days between the date of year end of the company until the date of signing of audit reports, company size measured by normal logarithm of total assets, the auditor opinions, earnings or losses of the company, reporting extraordinary items and/or contingency are measured with dummy variable, debt proportion measured by debt to asset ratio. Object of research is companies that have been registered on the Stock Exchange from the year 2008-2010 as many as 289 companies. The data obtained from the IDX website and Indonesian Capital Market Directory. Analysis of data using multiple linier regression. The analysis showed that the size of the company, auditor opinion, reporting extraordinary items and/or contingency affect the audit report lag. Gains or losses do not affect the company's audit report lag because auditors are still looking reasonable losses suffered by the company given the instability of economic conditions that occurred since 2008. Debt proportion does not affect the audit report lag because the auditor has considered the estimate time to complete the process of auditing responsibility in a timely manner.